Lyric Opera of Chicago : setting the scene to grow ticket sales - Lecinski, Jim; Masko, John (London : Kellogg School of Management, 2023)
In the summer of 2022, the Lyric Opera of Chicago (Lyric), a major opera company, is facing a deepening challenge. Lyric has seen ticket sales decrease, declining from 54% of revenue in 1998 to 33% by 2018. Since 2010, the primary source of this decline has been a loss in subscribers-high-value patrons who attend several operas per year. This subscriber lack is concerning not just for the lost ticket sales but also because subscribers are far more likely than single-ticket buyers to make gifts (a stream that now constitutes 51% of Lyric’s revenue). As it plans to counter this downward trend, Lyric’s marketing team has two questions to answer: First, the team must decide which audiences to focus on to fill its empty seats-past subscribers, "opera-primed" lookalikes of past subscribers, more diverse audiences closer to Chicago’s urban core, or millennials; then, once the team chooses a target audience, it must determine how Lyric should address that audience with its product, customer experience, and opera programming choices.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Marketing -- Decision making -- Case studies; Strategic planning -- Case studies; Decision making -- Case studies